Neutralizing antibody and CD8+ T cell responses following BA.4/5 bivalent COVID-19 booster vaccination in adults with and without prior exposure to SARS-CoV-2 - Underwood, Alexander P.; Sølund, Christina; Jacobsen, Kivin; Binderup, Alekxander; Fernandez-Antunez, Carlota; Mikkelsen, Lotte S.; Inekci, Dilek; Villadsen, Signe Lysemose; Castruita, Jose A. S.; Pinholt, Mette; Fahnøe, Ulrik; Ramirez, Santseharay; et al. (Frontiers in Immunology, 2024)
As severe acute respiratory coronavirus 2 (SARS-CoV-2) variants continue to emerge, it is important to characterize immune responses against variants which can inform on protection efficacies following booster vaccination. In this study, neutralizing breadth and antigen-specific CD8+ T cell responses were analyzed in both infection-naïve and infection-experienced individuals following administration of a booster bivalent Wuhan-Hu-1+BA.4/5 Comirnaty® mRNA vaccine. Significantly higher neutralizing titers were found after this vaccination compared to the pre-third booster vaccination time point. Further, neutralizing breadth to omicron variants, including BA.1, BA.2, BA.5, BQ.1 and XBB.1, was found to be boosted following bivalent vaccination. SARS-CoV-2-specific CD8+ T cells were identified, but with no evidence that frequencies were increased following booster vaccinations. Spike protein-specific CD8+ T cells were the only responses detected after vaccination and non-spike-specific CD8+ T cells were only detected after infection. Both spike-specific and non-spike-specific CD8+ T cells were found at much lower frequencies than CD8+ T cells specific to cytomegalovirus (CMV), Epstein-Barr virus (EBV) and influenza (Flu). Taken together, these results show that the bivalent Wuhan-Hu-1+BA.4/5 Comirnaty® mRNA vaccine boosted the breadth of neutralization to newer circulating SARS-CoV-2 variants and that vaccination is able to induce spike protein-specific CD8+ T cell responses, which are maintained longitudinally.